2016
DOI: 10.1055/s-0042-105872
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Patients with Breast Cancer in the Adjuvant and Metastatic Setting to Use Electronic Surveys (ePRO) Depends on Sociodemographic Factors, Health-related Quality of Life, Disease Status and Computer Skills

Abstract: Introduction: Because of the often unfavorable prognosis, particularly for patients with metastases, health-related quality of life is extremely important for breast cancer patients. In recent years, data on patient-relevant endpoints is being increasingly collected electronically; however, knowledge on the acceptance and practicability of, and barriers to, this form of data collection remains limited. Material and Methods: A questionnaire was completed by 96 patients to determine to what extent existing compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 43 publications
5
40
2
5
Order By: Relevance
“…Since systematic palliative treatment has only limited effect on survival rates, the concept of Healthrelated Quality of Life (HRQoL) and measurement of Patient-Reported Outcomes (PRO) is gaining more and more importance in the therapy setting of progressive diseases such as breast cancer, especially in the adjuvant or metastatic setting [6][7][8][9][10]. Cancer patients often suffer from symptoms and adverse events during their treatment, which are sometimes underestimated in clinical routine [11][12][13].…”
Section: Patient-reported Outcomes and Health-related Quality Of Lifementioning
confidence: 99%
See 4 more Smart Citations
“…Since systematic palliative treatment has only limited effect on survival rates, the concept of Healthrelated Quality of Life (HRQoL) and measurement of Patient-Reported Outcomes (PRO) is gaining more and more importance in the therapy setting of progressive diseases such as breast cancer, especially in the adjuvant or metastatic setting [6][7][8][9][10]. Cancer patients often suffer from symptoms and adverse events during their treatment, which are sometimes underestimated in clinical routine [11][12][13].…”
Section: Patient-reported Outcomes and Health-related Quality Of Lifementioning
confidence: 99%
“…Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,[36][37][38][39][40].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
See 3 more Smart Citations